Studi Literatur Identifikasi Jamur Pada Kuku dan Sela Kaki Penderita Diabetes Melitus - Anita, Anita; Aziz, Nurul Ni’ma; Fatmawati, Andi; Moiyo, Novalin (Lontara Journal of Health Science and Technology, 2020)
Diabetes mellitus is a disease characterized by hyperglycemia (increased blood sugar levels) that occurs due to abnormalities in insulin secretion, insulin action or both. High blood glucose levels can cause an increase in glucose levels in the skin of diabetes mellitus patients, thereby facilitating the appearance of skin manifestations in the form of dermatitis, bacterial infections, fungal infections and others. The condition of epithelial and mucosal cells of diabetes mellitus sufferers has increased adhesion to several groups of fungi on epithelial cells, namely mold and yeast. This type of research is a literature study that summarizes as many as 10 journals that are relevant to these studies. From the literature study, it turned out that 225 samples were obtained with details of 65 samples (28.9%) tested positive for Trichophyton rubrum, Trichophyton mentagrophytes, Epidermophyton floccosum and 160 samples (71.1%) tested negative. Based on the data from the literature study, it can be concluded that people with diabetes mellitus are at risk of being infected with the fungi that cause tinea pedis and tinea ungium, because the condition of the epithelial and mucosal cells has increased so that it makes it easier to develop fungal infections.